Patient accounts of diagnostic testing for familial hypercholesterolaemia: comparing responses to genetic and non-genetic testing methods - Hollands Gareth J; Armstrong David; Macfarlane Angela; Crook Martin A; Marteau Theresa M (BMC, 2012)
Abstract Background Continuing developments in genetic testing technology together with research revealing gene-disease associations have brought closer the potential for genetic screening of populations. A major concern, as with any screening programme, is the response of the patient to the findings of screening, whether the outcome is positive or negative. Such concern is heightened for genetic testing, which it is feared may elicit stronger reactions than non-genetic testing. Methods This paper draws on thematic analysis of 113 semi-structured interviews with 39 patients being tested for familial hypercholesterolaemia (FH), an inherited predisposition to early-onset heart disease. It examines the impact of disease risk assessments based on both genetic and non-genetic information, or solely non-genetic information. Results The impact of diagnostic testing did not seem to vary according to whether or not genetic information was used. More generally, being given a positive or negative diagnosis of FH had minimal discernible impact on people's lives as they maintained the continuity of their beliefs and behaviour. Conclusions The results suggest that concerns about the use of genetic testing in this context are unfounded, a conclusion that echoes findings from studies in this and other health contexts.